Varieties of Entrepreneurial Capitalism: The Culture of Entrepreneurship and Structural Inequalities of Work and Business Creation. Issue 10 (October 2016) - Doody, Sean; Chen, Victor Tan; Goldstein, Jesse
Abstract: As the labor market has changed over recent decades, a distinctive culture has evolved in tandem, epitomized by the innovation and dynamism of Silicon Valley. This culture of entrepreneurship celebrates autonomy and risk‐taking, legitimizes a shift toward flexible, contingent, and precarious work, and compels workers to continuously network, self‐improve, and self‐promote. This culture has helped to disseminate entrepreneurial practices to sectors of the economy traditionally characterized by stability and job security. We shed light on these changes by putting forward a new typology distinguishing between four ideal types of entrepreneurial activity: Silicon Valley entrepreneurship, Main Street entrepreneurship, corporate entrepreneurship, and entrepreneurial self‐employment. Each adopts the language and normative behaviors of the culture of entrepreneurship, but the 'entrepreneurs' working within these domains enjoy starkly different levels of creative and financial autonomy. Integrating scholarship on economic sociology, work and labor, cultural sociology, and critical theory, we explore the underlying dynamics of entrepreneurship that cut across institutional contexts in unexpected and sometimes contradictory ways. The conceptual understanding of entrepreneurship we put forward recognizes both entrepreneurship's relationship to past forms of business creation and its contemporary cultural influence, while also underscoring the various constraints and inequalities intrinsic to these forms of market activity.